ANALISA PERSEBARAN LITOLOGI SANDSTONE PADA FORMASI TALANG AKAR MENGGUNAKAN INVERSI EXTENDED ELASTIC IMPEDANCE (EEI) DI LAPANGAN CILAMAYA, CEKUNGAN JAWA BARAT UTARA - Ophi Thio Rendy; Agus Setyawan; Muhammad Mualimin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Extended Elastic Impedance (EEI) inversion method has been used to analyze sandstone lithology distribution of Talang Akar Formation in Cilamaya Field, North West Java Basin. The target zone was Z2230 layer which located in Talang Akar Formation with litologies of sandstone and shale. Sensitivity analysis showed that gamma-ray and density are sensitive to discriminate the type of lithologies in Z2230 target layer. EEI(58) could simulate gamma-ray and EEI(12) could simulate density with respectively 0,397 and 0,613 correlation values. EEI(12) inversion result showed sandstone lithology distribution in Z2230 layer with 8800 to 9800 . Sandstone lithology distribution concentrated in northwest–southeast of study area. There was hydrocarbon prospect area in north of well OTR-10.Keywords : Extended Elastic Impedance (EEI), gamma-ray, density, sandstone